2022
DOI: 10.1159/000524961
|View full text |Cite
|
Sign up to set email alerts
|

Bone Turnover, Mineralization, and Volume Estimated by <sup>18</sup>F-Sodium Fluoride PET/CT and Biomarkers in Chronic Kidney Disease: Mineral and Bone Disorder Compared with Bone Biopsy

Abstract: <b><i>Introduction:</i></b> Invasive bone biopsy to assess bone metabolism in patients with chronic kidney disease-mineral and bone disorder may be replaced by the noninvasive <sup>18</sup>F-NaF PET/CT and biomarkers of bone metabolism. We aimed to compare parameters of bone turnover, mineralization, and volume assessed by bone biopsies with results derived from <sup>18</sup>F-NaF PET/CT and biomarkers (bone-specific alkaline phosphatase, osteocalcin, fibroblast … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…For 18 F, this hypothesis is supported by a study by Reeve et al in patients with postmenopausal osteoporosis that reported correlations between bone blood flow measured using [ 18 F]NaF, bone turnover measured using [ 85 Sr]SrCl 2 , and dynamic bone histomorphometry performed at the iliac crest (11). It is also supported by more recent studies that have examined the correlations between K i measurements at the spine and hip and indices of bone formation measured by bone biopsy in patients with chronic kidney disease mineral and bone disorder (CKD-MBD) (3,4).…”
Section: What Is Bone Remodelling?mentioning
confidence: 81%
See 4 more Smart Citations
“…For 18 F, this hypothesis is supported by a study by Reeve et al in patients with postmenopausal osteoporosis that reported correlations between bone blood flow measured using [ 18 F]NaF, bone turnover measured using [ 85 Sr]SrCl 2 , and dynamic bone histomorphometry performed at the iliac crest (11). It is also supported by more recent studies that have examined the correlations between K i measurements at the spine and hip and indices of bone formation measured by bone biopsy in patients with chronic kidney disease mineral and bone disorder (CKD-MBD) (3,4).…”
Section: What Is Bone Remodelling?mentioning
confidence: 81%
“…The link between quantitative measurements of [ 18 F]NaF kinetics and bone formation rate is supported by a study by Reeve et al that used both [ 18 F]NaF and [ 85 Sr]SrCl 2 together with dynamic bone histomorphometry to establish correlations between skeletal blood flow, calcium-surrogate bone mineral uptake, and mineral apposition rate in patients with postmenopausal osteoporosis (11). In more recent studies, bone metabolic flux (K i ) values obtained using [ 18 F]NaF PET have been compared with measurements of bone formation rate made by the gold standard method of bone biopsy in patients with CKD-MBD (Figure 4) (3,4). By comparison with [ 18 F]NaF PET-CT, bone biopsy is a painful and complex procedure that is limited to a single biopsy site at the iliac crest, is subject to significant measurement errors and is now rarely performed, with many centres not having the necessary resources.…”
Section: What Is Bone Remodelling?mentioning
confidence: 99%
See 3 more Smart Citations